Medication recommendations in the updated NICE guideline for the treatment and management of schizophrenia - Barnes, T. R. E.; Paton, C. (Die Psychiatrie, 2010)
The NICE guideline titled, „Schizophrenia: core interventions in the treatment and management of schizophrenia in adults in primary and secondary care“, appeared in 2002, and was the first NICE guideline to be published. It was updated in 2009, and this article comments on some of the revised recommendations relating to pharmacotherapy. The accumulating evidence influencing the recommendations relating to informed choice of antipsychotic, the use of high dose and combined antipsychotics and the assessment and monitoring of side effects is reviewed. The impact of such guidelines, and the extent to which clinical practice in the UK complies with some of the key pharmacological recommendations, are also addressed.
Keywords: Treatment guidelines; schizophrenia; antipsychotic drugs